EFEK SAMPING EKSTRAK ETANOL 96% DAN 70% HERBA KEMANGI (Ocimum americanum L.) YANG BERSIFAT ESTROGENIK TERHADAP KADAR ASAM URAT PADA TIKUS PUTIH - Rina Siti Nurul Husna; E. Mulyati Effendi; Hera Maheshwari (EKOLOGIA, 2016)
The aims of study was determine the effect of 70% and 96% ethanolic extracted of estrogenic herb basil on increasing or decreasing the level of uric acid in female rats. The animals used were 24 rats that were divided into six groups which consist of four animals each. Group I was animal that were given at a dose 0,7g/200g BW of 70% ethanolic extracted basil. Group II was the same concentration of basil extract at a dose 0,8g/200g BW. Group III was also the concentration of basil extract at a dose 0,9g/200g BW. Group IV was animals that were given at a dose 0,7g/200g BW of 96% ethanolic extracted basil. Group V was the same concentration of basil extract at a dose 0,8g/200g BW. Group VI was also the concentration of basil extract at a dose 0,9g/200g BW. The result showed that the ethanol extract of the basil herb had no significantly affected uric acid, there was even a tendency to decrease lower uric acid level after given during 15 days.Key words : Uric Acid, Estrogenic, Herb Basil